Emergency cardiac care in the athletic setting: from schools to the Olympics. (24th October 2012) - Toresdahl, Brett; Courson, Ron; Börjesson, Mats; Sharma, Sanjay; Drezner, Jonathan
Abstract : Medical providers at sporting events must be well-trained in the care of cardiac emergencies. Optimal outcomes are most likely achieved through comprehensive emergency planning that ensures prompt and appropriate care. The diversity of athletic venues, as well as the age and competition level of different athlete populations, present challenges to the provision of appropriate emergency care in sport. An efficient and coordinated medical response to cardiac emergencies requires an established emergency action plan, training of potential first responders in cardiopulmonary resuscitation and use of an automated external defibrillator, coordinating communication and transportation systems, and ensuring access to appropriate medical equipment and supplies. Prompt recognition and early defibrillation are critical in the management of athletes suffering sudden cardiac arrest. This article reviews emergency planning and cardiac care in athletics, with special considerations presented for the school, large arena, mass event and Olympic settings.